The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/eji.200535178
|View full text |Cite
|
Sign up to set email alerts
|

A mutant human IgG molecule with only one C1q binding site can activate complement and induce lysis of target cells

Abstract: There are potentially two binding sites for C1q on IgG, one on each CH2 domain of the gamma heavy chains, close to the lower hinge region. It is not clear whether the presence and involvement of both the C1q binding sites is necessary to induce the activation signal of human IgG. In order to clarify this issue, we made a hybrid mutant IgG1/IgG3 molecule where the IgG1 half of the molecule was made unable to activate complement through the introduction of a P329A mutation. The IgG3 half of the molecule was muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…The residues K322, P329 and P331 are crucial for complement activation for both IgG1 [5,7,21,23] and verified for K322 of IgG3 [8,23] and for P329 and P331 of IgG3 in this report. Interestingly, when mutation at position 329 was mutated from proline to alanine was performed on the basis of IgG3h1 (IgG3 with a hinge of IgG1), the resulting IgG3h1P329A molecule was devoid of ADCML activity even at high target antigen concentration [33]. Apparently residue proline 329 is even more crucial for ADCML activity, at least for IgG3, than residue lysine 322.…”
Section: Residues Lys322 Pro329 and Pro331mentioning
confidence: 99%
“…The residues K322, P329 and P331 are crucial for complement activation for both IgG1 [5,7,21,23] and verified for K322 of IgG3 [8,23] and for P329 and P331 of IgG3 in this report. Interestingly, when mutation at position 329 was mutated from proline to alanine was performed on the basis of IgG3h1 (IgG3 with a hinge of IgG1), the resulting IgG3h1P329A molecule was devoid of ADCML activity even at high target antigen concentration [33]. Apparently residue proline 329 is even more crucial for ADCML activity, at least for IgG3, than residue lysine 322.…”
Section: Residues Lys322 Pro329 and Pro331mentioning
confidence: 99%
“…Lys B136 was selected as a residue from the apo plane, which is located near the bottom side of ghB and far away from any proposed binding site. (31)(32)(33)(34)(35). Chemical modification, mutational analysis, and molecular modeling approaches have been used to dissect the complementary IgG binding sites on the gC1q domain (7,10,11,19).…”
Section: Certain Key Residues Belonging To the Apo And Holo Planes Ofmentioning
confidence: 99%
“…By immuno-histochemical methods and radioimmunoassay, we and others have previously shown that IgG2b binding to AChR at the neuro-muscular junction (NMJ), triggers complement activation that leads to formation of the membrane attack complex (MAC), which depletes functional muscle AChRs at the NMJ (Nakano and Engel, 1993; Kusner and Kaminski, 2012; Tüzün and Christadoss, 2013). Complement activation by anti-AChR antibody is required for AChR depletion and EAMG development (Michaelsen et al, 2006). However, while mouse IgG2b (as well as mouse IgG2a and IgG3 and human IgG1 and IgG3) effectively activates the classical complement cascade, mouse IgG1 and human IgG2 and IgG4 have little or no ability to do this (Redpath et al, 1998).…”
Section: Introductionmentioning
confidence: 99%